0073 Activation of Leptin Receptor Positive Neurons in the Nucleus of The Solitary Tract (NTS) Alleviates Sleep Disordered Breathing in Obese Mice. (12th April 2019) - Freire, Carla; Pho, Huy; Berger, Slava; Fleury-Curado, Thomaz; Sennes, Luiz U; Schwartz, Alan R; Polotsky, Vsevolod Y
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is a major cause of morbidity and mortality with high prevalence. The loss of motor input related to deeper sleep stages lead to recurrent pharyngeal collapse (apneas and hypopneas), leading to oxyhemoglobin desaturations and arousals. There is still no effective pharmacotherapy for OSA. Leptin is a powerful respiratory stimulant and long isoform of leptin receptor, LepRb in the brain is an important therapeutic target in sleep disordered breathing. Methods: Male LepR b -Cre mice with diet induced obesity (DIO) underwent bilateral stereotactic administration to NTS of an adeno-associated virus harboring the excitatory Cre -dependent Designer Receptor Exclusively Activated by Designer Drug (DREADD) rAAV5.2-hSyn-DIO-hM3(Gq)-mCherry (Virovek, 1 x 101 3 vg/ml, 250 nl) (n = 4) and headmount with EEG and nuchal EMG leads under 1-2% isoflurane. Four-six weeks later, sleep studies were performed after DREADD ligand (JH37160) or saline i.p. injection in a randomized blinded manner. Treatment groups were crossed-over and sleep studies were repeated a week later. Results: We successfully targeted NTS with DREADDs. JH37160 dramatically increased non-flow limited minute ventilation (VE ) from 0.92±1.32 mL/min/g to 1.34±0.39 mL/min/g in NREM sleep and from 0.89±0.43 mL/min/g to 1.24±0.53 mL/min/g in REM sleep without change in body temperature suggesting up-regulation of ventilatory control rather than a metabolic response. There was no decrease in the frequency of obstructed breaths. However, upper airway obstruction significantly improved which was manifested by an increase in maximal inspiratory flow (from 2.1±7.3 mL/s to 3.8±0.9 mL/s in NREM and from 2.5±0.8 mL/s to 3.6±0.8 mL/s in REM) and minute ventilation (from 0.73±0.3 mL/min/g to 1.29±0.4 mL/min/g in NREM and from 0.96±0.46 mL/min/g to 1.19±0.49 mL/min/g in REM) during obstructed breathing. This improvement resulted in striking decreases in the oxyhemoglobin desaturation index, which decreased from 37.1 to 4.4 events/hr in REM sleep. Conclusion: Activation of LepR b + neurons in NTS alleviates sleep disordered breathing in DIO mice affecting both ventilatory and upper airway control. Support (If Any): NIH R01 HL128970, NIH R01 138932, FAPESP: 2018/08758-3, CNPq: 142073/2017-2